Differential Neutralization of Apixaban, Betrixaban, Edoxaban, and Rivaroxaban by Andexanet Alfa as Measured by Whole Blood Thromboelastographic Analysis. (December 2022) - Mehrotra, Siddharth; Hoppensteadt, Debra; Jeske, Walter; Siddiqui, Fakiha; Iqbal, Omer; Tafur, Alfonso; Lewis, Bruce; Jaradeh, Mark; Kantarcioglu, Bulent; Fareed, Jawed
Introduction: The available oral anti-Xa agents are routinely used for the management of thrombotic disorders. A molecularly modified recombinant coagulation FXa, also known as Andexanet Alfa (AA), that has been developed as an antidote to neutralize the bleeding effects of oral FXa inhibitors, such as Apixaban and Rivaroxaban. Materials and Methods: This study utilized thromboelastography (TEG 5000 Hemostasis System), to investigate the neutralizing effects of AA at different concentrations of oral FXa inhibitors measuring such parameters as R-Time, K-Time, Angle, and Max Amplitude (MA). Apixaban, Betrixaban, Edoxaban, and Rivaroxaban were obtained commercially in powdered form. Each of these drugs was supplemented with freshly drawn whole citrated blood at a concentration of 1 μg/mL. And subsequently mixed with AA at 50 or 100 μg/mL. Results: At a concentration of 1 μg/mL, all FXa inhibitors produced variable anticoagulant effects in the order of Edoxaban > Betrixaban > Rivaroxaban > Apixaban. AA at 100 μg/mL produced a complete neutralization of these inhibitors whereas at 50 μg/mL relatively weaker neutralization as measured by various parameters. Conclusion: These results suggest that regardless of the variable anticoagulant effects exhibited by the FXa Inhibitors, AA at FC = 100 μg/mL fully neutralized these agents as measured by the TEG parameters. AA was shown to be more effective in neutralizing Betrixaban and least effective in Apixaban. The neutralization of various FXa inhibitors was dose and donor-dependent warranting dosage adjustment for optimal outcomes.